Adjustment Of TER Rates For Income Tax Article 21 For Corporate Taxpayers In CV. Kirana Cahaya Sejahtera Gunungsitoli - Fonahia Ndruru; Sophia Molinda Kakisina (UNIVED Press, 2026)
This study aims to determine the calculation, withholding, and reporting system for Article 21 Income Tax for Employees at CV. Kirana Cahaya Sejahtera and to find solutions to existing problems related to the calculation, withholding, and reporting system for Article 21 Income Tax for Employees. In conducting this study, the researcher used a descriptive research method. Data collection techniques used were observation, interviews, and documentation. The collected data were analyzed using qualitative descriptive analysis techniques and deductive and inductive methods. The results of the study indicate that CV. Kirana Cahaya Sejahtera's system for calculating, depositing, and reporting Article 21 Income Tax for employees is quite good and adequate. However, the company has not been able to withhold Article 21 Income Tax in accordance with the Tax Law. Furthermore, the system for calculating Article 21 Income Tax for permanent employees does not match the calculated Article 21 Income Tax payable according to CV. Kirana Cahaya Sejahtera and the calculated Article 21 Income Tax payable according to the researcher, referring to Government Law No. 58 of 2023. This is because overtime pay given every month to employees is not included as an addition to gross income, because according to the company, what is included as an addition to gross income is only income that is regularly received in the same period (in this case every month), also in the same amount (in this case basic salary and attendance money). What should be correct according to Law No. 58 of 2023, overtime pay is one of the components that increase gross income. It is because of these considerations that there is a difference in underpayment between Article 21 Income Tax that has been deducted by the company and the researcher.